2016
DOI: 10.1080/15374416.2015.1105138
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Sequencing for Childhood ADHD: A Multiple-Randomization Study of Adaptive Medication and Behavioral Interventions

Abstract: Objective Behavioral and pharmacological treatments for children with ADHD were evaluated to address whether endpoint outcomes are better depending on which treatment is initiated first, and, in case of insufficient response to initial treatment, whether increasing dose of initial treatment or adding the other treatment modality is superior. Methods Children with ADHD (ages 5–12, N = 146, 76% male) were treated for one school year. Children were randomized to initiate treatment with low doses of either (a) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 59 publications
(74 reference statements)
6
145
0
13
Order By: Relevance
“…Parents identified the joint parent/child sessions as a particular strength. Even though treatment with psychostimulants has been found to reduce attendance rates for behavioral therapies, 68 only two (6%) families failed to attend the majority of sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Parents identified the joint parent/child sessions as a particular strength. Even though treatment with psychostimulants has been found to reduce attendance rates for behavioral therapies, 68 only two (6%) families failed to attend the majority of sessions.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, additional investigations should evaluate what are the active components of our LBM and HBM behavioral treatment strategies. Pelham and colleagues have begun to investigate which is the best sequence in which to introduce interventions (behavioral, pharmacological, or combined) and which is the best way to enhance initial treatment for nonresponders to low-dose treatments (Pelham, Fabiano, et al, 2013), as well as the cost effectiveness of combined treatment relative to higher doses of unimodal treatment (Page et al, 2013), and what child and family characteristics influence response. Finally, will these effects be replicable in home and school settings, and can the combined low dose intervention be shown to have long-term benefits?…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that sequencing psychosocial treatment before medication treatment reduces the dose and overall exposure of medication 33 and increases parents' engagement in behavioral interventions. 34 There are several limitations of the study. First, the sample may not be representative of children who typically present to clinics with complaints related to ADHD.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%